A DNA Molecular Robot that Autonomously Walks on the Cell Membrane to Drive Cell Motility. Issue 50 (5th November 2021) - Li, Hao; Gao, Jing; Cao, Lei; Xie, Xuan; Fan, Jiahui; Wang, Hongda; Wang, Hong‐Hui; Nie, Zhou
Abstract: Synthetic molecular robots can execute sophisticated molecular tasks at nanometer resolution. However, a molecular robot capable of controlling cellular behavior remains unexplored. Herein, we report a self‐propelled DNA robot operating on the cell membrane to control the migration of a cell. Driven by DNAzyme catalytic activity, the DNA robot could autonomously and stepwise move on the membrane‐floating cell‐surface receptors in a stochastic manner and simultaneously trigger the receptor‐dimerization to activate downstream signaling for cell motility. The cell membrane‐associated continuous motion and operation of a DNA robot allowed for the ultrasensitive regulation of MET/AKT signaling and cytoskeleton remodeling to enhance cell migration. Finally, we designed distinct conditional DNA robots to orthogonally manipulate the cell migration in a coculture of mixed cell populations. We have developed a novel strategy to engineer a cell‐driving molecular robot, representing a promising avenue for precise cell manipulation with nanoscale resolution. Abstract : A DNA molecular robot that autonomously walks on the cell membrane to drive the cell motility has been developed. The DNA robot could move stepwise on the membrane‐floating cell‐surface receptors in a stochastic manner and simultaneously trigger the receptor‐dimerization to activate downstream signal pathway regulation of desired cellular behavior.